Sequential soil washing techniques using hydrochloric acid and sodium hydroxide for remediating arsenic-contaminated soils in abandoned iron-ore mines - Jang, Min; Hwang, J.S.; Choi, S.I. (Elsevier, 2007)
Sequential washing techniques using single or dual agents sodium hydroxide (NaOH) and hydrochloric acid (HCl) solutions were applied to arsenic-contaminated soils in an abandoned iron-ore mine area. We investigated the best remediation strategies to maximize arsenic removal efficiency for both soils and arsenic-containing washing solution through conducting a series of batch experiments. Based on the results of a sequential extraction procedure, most arsenic prevails in Fe-As precipitates or coprecipitates, and iron exists mostly in the crystalline forms of iron oxide. Soil washing by use of a single agent was not effective in remediating arsenic-contaminated soils because arsenic extractions determined by the Korean standard test (KST) methods for washed soils were not lower than 6 mg kg-1 in all experimental conditions. The results of X-ray diffraction (XRD) indicated that iron-ore fines produced mobile colloids through coagulation and flocculation in water contacting the soils, containing dissolved arsenic and fine particles of ferric arsenate-coprecipitated silicate. The first washing step using 0.2 M HCl was mostly effective in increasing the cationic hydrolysis of amorphous ferrihydrite, inducing high removal of arsenic. Thus, the removal step of arsenic-containing flocs can lower arsenic extractions (KST methods) of washed soils. Among several washing trials, alternative sequential washing using 0.2 M HCl followed by 1 M HCl (second step) and 1 M NaOH solution (third step) showed reliable and lower values of arsenic extractions (KST methods) of washed soils. This washing method can satisfy the arsenic regulation of washed soil for reuse or safe disposal application. The kinetic data of washing tests revealed that dissolved arsenic was easily readsorbed into remaining soils at a low pH. This result might have occurred due to dominant species of positively charged crystalline iron oxides characterized through the sequential extraction procedure. However, alkaline extraction using NaOH was effective in removing arsenic readsorbed onto the surface of crystalline minerals. This is because of the ligand displacement reaction of hydroxyl ions with arsenic species and high pH conditions that can prevent readsorption of arsenic. Â© 2006 Elsevier Ltd. All rights reserved.